Exploring English Majors’ Experience in Improving Their English-Speaking Skills: A Fenomenology Study - Nadia Abdjul; Abid; Hasanuddin Fatsah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study explores the experiences of English major students in improving their English-speaking skills after completing one year of study in the English Language Education Study Program at Universitas Negeri Gorontalo. It aims to understand how students perceive their speaking development and identify factors that support or hinder their progress. The study used a qualitative descriptive phenomenological design to capture students lived experiences. Ten third-semester English major students were selected purposively as participants. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings show that students’ speaking development is influenced by both positive and negative learning experiences. Positive experiences include support from lecturers and peers, collaborative learning, intrinsic motivation, and increased self-confidence, which encourage students to participate actively in speaking activities. Meanwhile, negative experiences include anxiety, fear of negative judgment, and avoidance behavior, influenced by personal insecurities and classroom dynamics. Based on the emotional geography framework, students’ speaking experiences are related to sociocultural, moral, professional, political, and physical dimensions of the learning environment. These findings suggest that speaking challenges are not only linguistic but also influenced by emotional and social interactions.